Outcomes of definitive radiotherapy for early laryngeal cancer in terms of survival and patterns of failure. Issue 12 (3rd December 2019) - Adeel, M; Faisal, M; Rashid, A; Rasheed, S; Hussain, R; Malik, K I; Hameed, M Y; Jamshed, A
Abstract: Background: Early laryngeal cancer treated with definitive radiotherapy or surgery has a high cure rate. This study evaluated the patterns of treatment failure and long-term results of early laryngeal cancers treated with definitive radiotherapy. Method: From January 2002 to December 2014, a total of 242 patients with early-stage laryngeal cancers were treated with radical radiotherapy. Results: All patients had squamous cell carcinoma of the larynx (92 per cent male and 8 per cent female). Median follow-up was 4.5 years. The majority of patients were smokers (57.4 per cent). Local failure was seen in 12.5 per cent of stage I patients and 22.8 per cent of stage II patients. The 5-year overall survival and disease specific survival were 84 per cent and 91 per cent, respectively. Conclusion: In summary, radiotherapy is a suitable treatment modality for patients with early-stage laryngeal cancer, with an overall locoregional control rate of 84 per cent. Patients who fail radiotherapy may still undergo salvage laryngectomy.